2017
DOI: 10.1002/jsfa.8290
|View full text |Cite
|
Sign up to set email alerts
|

Genotype‐by‐environment effect on bioactive compounds in strawberry (Fragaria x ananassa Duch.)

Abstract: A 'plant environmental metabolomics' approach has been used successfully to assess the phenotypic plasticity of varieties that showed different magnitudes with respect to the relationship between environmental conditions and the accumulation of healthy compounds. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 49 publications
3
20
1
1
Order By: Relevance
“…The polyphenol composition of these two genotypes when fully ripe differed from their values in our genotype comparison [8]. Polyphenol composition has been shown to depend on factors such as genotype, maturity stage, and production site and environment [9,10,16,[36][37][38][39]. The differing results may be due to one or more of these factors, but the most likely cause was production environment as the genotype comparison was performed with fruit from greenhouse-grown plants during the winter and this developmental study was from the same set of plants but grown outdoors under natural light and ambient conditions in summer.…”
Section: Polyphenol Content-development Stagesmentioning
confidence: 65%
See 1 more Smart Citation
“…The polyphenol composition of these two genotypes when fully ripe differed from their values in our genotype comparison [8]. Polyphenol composition has been shown to depend on factors such as genotype, maturity stage, and production site and environment [9,10,16,[36][37][38][39]. The differing results may be due to one or more of these factors, but the most likely cause was production environment as the genotype comparison was performed with fruit from greenhouse-grown plants during the winter and this developmental study was from the same set of plants but grown outdoors under natural light and ambient conditions in summer.…”
Section: Polyphenol Content-development Stagesmentioning
confidence: 65%
“…The types and levels of these secondary metabolites vary among commercial strawberry cultivars (F. x ananassa Duch.) [2,3], as well as in the wild species F. chiloensis [4,5], F. pentaphylla [6] and F. vesca [7,8] The variation among cultivars is due to genotype, cultural practices, the production environment, and their interaction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, TFC and TAC were significantly (P < 0.05) higher in the 'Albion' cultivar. A previous study by Palmieri et al 17 demonstrated the effect of genotype and environmental conditions on the nutrient content in nine strawberry cultivars. According to those results, 'Albion' was the most sensitive of the nine in responding to the different environmental conditions.…”
Section: Effect Of High Temperature and E[co 2 ] On Total Polyphenolsmentioning
confidence: 97%
“…9,[11][12][13] However, the strawberry polyphenol profile can vary widely qualitatively and quantitatively as it is affected by various factors, including genotype, environmental factors, and their interactions. [14][15][16][17][18][19][20][21] The genetic makeup of strawberries is the most critical contributory factor in the variability of the nutritional quality of fruits in terms of total polyphenol content (TPC), total antioxidant content (TAC) and levels of individual polyphenols; however, growing conditions or environmental factors also play a significant role in determining the nutritional value of strawberries. 14,16,18 Both genotype and environmental factors have been reported to influence the chemical composition of strawberry significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation